2007
DOI: 10.4049/jimmunol.179.11.7808
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAPK by Reactive Oxygen Species Is Essential in a Rat Model of Stress-Induced Gastric Mucosal Injury

Abstract: Stress ulceration is a common complication in critically ill patients and can result in significant upper gastrointestinal bleeding associated with a high morbidity and mortality. At present, little is known of the molecular mechanisms underlying the incidence of this type of gastric damage. In the present study, we investigated the temporal activation of the redox-sensitive p38 signaling transduction cascade and its roles in a well-defined experimental model of cold immobilization stress-induced gastric ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 49 publications
(73 reference statements)
2
62
0
1
Order By: Relevance
“…Previous studies have showed that treatment with p38 MAPK and JNK kinases inhibitors could lessen cold constraint stress-induced tissue injury [2,19]. Our studies exhibited that pre-treatment with Hs also inhibited the excessive P-p38 MAPK and P-JNK activity, but not total JNk and p38 MAPK (Fig.…”
Section: Hs Inhibited the Activity Of P-p38 Mapk P-jnk And Nf-κbsupporting
confidence: 60%
See 2 more Smart Citations
“…Previous studies have showed that treatment with p38 MAPK and JNK kinases inhibitors could lessen cold constraint stress-induced tissue injury [2,19]. Our studies exhibited that pre-treatment with Hs also inhibited the excessive P-p38 MAPK and P-JNK activity, but not total JNk and p38 MAPK (Fig.…”
Section: Hs Inhibited the Activity Of P-p38 Mapk P-jnk And Nf-κbsupporting
confidence: 60%
“…In the present study, we observed that pretreatment with hydrogen resulted in significantly decreased TNF-α, IL-1β and CINC-1 production and then prevented the subsequent neutrophils infiltration. This is a number of recent reports that showed that ROS-mediated p38 MAPK, JNK and NF-κB activation played an essential role in the pathogenesis of cold constraint stress-induced gastric damage [1,2,19]. To explore the downstream signaling mechanisms responsible for the roles of hydrogen to suppress proinflammatory cytokine production, we assessed how they affected the activation of P-p38 MAPK, P-JNK and NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was found that NF-kB activation played an important role in stress ulcer by increasing proinflammatory gene over expression in the gastric mucosa. In another study, it was indicated that there might be a pathway through which NF-kB and AP-1 activation is triggered by SOR and this was defined as the SOR/NF-kB pathway (43). In the same study, SOR/NF-kB pathway was shown to increase TNF-α, IL-1 and CINC-1and that AP-1, allowed for the transcription of genes such as C/EBP or Stat3 genes.…”
Section: Discussionmentioning
confidence: 97%
“…Histamine released during stress results an increase in gastric acid secretion and a decrease in mucous production, is known to be responsible for stress-induced ulcer (Jia et al, 2007). However, a significant reversal of ulcer score and ulcer index by ulcerene (50 and 100 mg/kg), suggests its ulcer curative potential, that can be related to the blockade of H2 receptors similar to ranitidine (50 mg/kg).…”
Section: Discussionmentioning
confidence: 99%